A strategy to design biocompatible polymer particles possessing increased loading efficiency and controlled-release properties - Pakawanit,P. (Royal Society of Chemistry, 2015)
Temperature-responsive poly(N-isopropylacrylamide), or poly(NIPAM), layers were reliably prepared around guest molecule (i.e., rhodamine B)-loaded mesoporous silica (SiO2) particles via thermally- and light-induced radical polymerizations. Subsequent removal of the sacrificial SiO2 particles with dilute hydrofluoric acid led to the formation of biocompatible polymer particles possessing a high dose of rhodamine B. The use of SiO 2 core templates not only led to the formation of a uniform coating of the poly(NIPAM) layers, but also increased the stability of the guest molecule, rhodamine B, throughout polymerization. Interestingly, the light-induced radical polymerization method resulted in much less inevitable leaching and decomposition of azo-based guest molecules. The structural information and overall dye-loading efficiency of the mesoporous particles and the final polymer particles were then thoroughly examined by electron microscopes, dynamic light scattering, and fluorescence spectroscopy. As poly(NIPAM)-based particles exhibited significant swelling and deswelling properties above and below the lower critical solution temperature, the controlled-release properties of the poly(NIPAM) particles prepared by both methods were also evaluated. Generally, the dye-loaded poly(NIPAM) particles prepared by the light-induced approach resulted in a thinner coating of the polymer layers and exhibited much higher loading and tunable release profiles of the loaded guest molecules than those prepared by the thermally-induced polymerization. Given these features, the generalization of our strategy to design chemotherapeutically interesting drug-loaded polymer particles that are biocompatible and sensitive to external stimuli will allow for the further development of novel biomedical delivery and treatment systems. © 2014 the Partner Organisations.